Bibliometric Mapping of Postoperative Wound Care Patient Education: Trends, Collaboration Networks, and Research Gaps (2019–2024) - Wijanarko, Wahyu; Cahyati, Widya Hari; Ningrum, Dina Nur Anggraini (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: Surgery is at risk of developing surgical wound infections (ILOs) that can prolong recovery and reduce the patient's quality of life. Wound care according to standards and education to patients and families are essential to prevent complications. The role of health workers as educators and optimal family support is key in accelerating postoperative healing. This study aims to analyze global and domestic literature bibliometrically to identify trends in publications, collaborations, research themes, and knowledge gaps, especially in Indonesia. Materials and methods: This research method uses a bibliometric approach by looking at data retrospectively. Data was collected from Scopus, PubMed, Garuda Portal, and Google Scholar (2019–2024), analyzed with VOSviewer and Biblioshiny. Results: The results of the 796 articles showed an increase in publications and strong collaboration between institutions in the US, China, and the UK. Four main clusters emerged: education and self-management, wound care technology, clinical outcomes and complication prevention, and the role of patient introduction. In Indonesia, research is still predominantly descriptive, with minimal technological exploration and a burden of parenting Conclusions: global research is moving towards technology and patient empowerment, while Indonesia lags behind in innovation and sustainability of interventions. The study recommends the development of culturally adaptive blended education models, evaluation of the cost-effectiveness of telemedicine, and measurement of long-term outcomes for patients and patient providers